2004
DOI: 10.1074/jbc.m311353200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of a Human Multisubstrate Specific Nucleotide-sugar Transporter Homologous to Drosophila fringe connection

Abstract: Nucleotide-sugar transporters are crucial components in the synthesis of glycoconjugates. We identified a novel human nucleotide-sugar transporter gene, hfrc1, which is homologous to Drosophila melanogaster fringe connection, Caenorhabditis elegans sqv-7, and human UGTrel7. HFRC1 was localized within the Golgi apparatus following its transient expression in HCT116 cells. In human tissues, hfrc1 and UGTrel7 exhibited similar tissue distributions, although hfrc1 transcripts showed a 10 times greater abundance th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 36 publications
(30 reference statements)
3
40
0
2
Order By: Relevance
“…The residual levels of monofucosylated N-glycans indicate that nac 1 flies are still able to transport some GDP-fucose into the Golgi. This suggests the presence of an alternative, functionally redundant GDP-fucose transport mechanism, a notion that is supported by the results of another study, in which faint anti-HRP and A. aurantia lec- (69), and humans (human FRC1 and hUGTrel7) (68,70).…”
Section: Discussionsupporting
confidence: 69%
“…The residual levels of monofucosylated N-glycans indicate that nac 1 flies are still able to transport some GDP-fucose into the Golgi. This suggests the presence of an alternative, functionally redundant GDP-fucose transport mechanism, a notion that is supported by the results of another study, in which faint anti-HRP and A. aurantia lec- (69), and humans (human FRC1 and hUGTrel7) (68,70).…”
Section: Discussionsupporting
confidence: 69%
“…GAGosome) (42,43), and it was demonstrated that overexpression of the nucleotide-sugar transporter HFRC1 induced accumulation of heparan sulfate (44). Interestingly, UDP-glucose pyrophosphorylase, which produces UDPglucose from glucose 1-phosphate, was reported to be O-GlcNAcylated (45).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, multisubstrate transporters of nucleotide sugars have been described in several organisms, including L. donovani (29), D. melanogaster (12), humans (20), E. histolytica (23), etc. A competitive substrate translocation mechanism has been since then assumed but not proven in any other study.…”
Section: Discussionmentioning
confidence: 99%
“…Although both transporters transport multiple substrates, it is only for SQV-7, the first described multisubstrate nucleotide sugar transporter, that competition among these substrates has been demonstrated. In all other cases, including mammals (20,21), insects (11,12), plants (22), and protista (23), where multiple substrates have been described for a given nucleotide sugar transporter, a competitive transport mechanism has been assumed but not shown.…”
Section: Co3h52 Transports Udp-glcnac and Udp-galnacmentioning
confidence: 99%